Oral and Maxillofacial Surgery - Kerawala, Cyrus; Newlands, Carrie (Oxford : Oxford University Press, 2020)
"Oral and Maxillofacial Surgery is the fully updated third edition of the essential guide for all of those working towards the FRCS OMFS exit exam or the Diploma of Membership of the Faculty of Dental Surgery (MFDS) assessment, as well as a handy quick reference for consultants working in the field. Providing a concise and structured overview of the current oral and maxillofacial practice, the handbook covers the diagnosis and surgical treatment of diseases affecting the mouth, jaws, face, and neck. Including a combination of clinical photographs and line drawings to aid understanding, the text has been bought in line with new evidence, practice, and revised guidelines, whilst maintaining the clear, user-friendly layout and expert tips of the previous editions"--
Revised edition of: Oral and maxillofacial surgery / [edited by] Cyrus Kerawala, Carrie Newlands. Second edition. 2014.
Includes bibliographical references and index.
Keywords: Mouth -- Surgery -- Handbooks, manuals, etc; Maxilla -- Surgery -- Handbooks, manuals, etc